The community capability in product development for the export of Nakhon Pathom province to Malaysia / Hathaipun Soonthornpipit ... [et al.] - Soonthornpipit, Hathaipun; Hotrawaisaya, Chattrarat; Hemapan, Salisa; Saensook, Peeranthon (2019)
At present, the ASEAN Economic Community has me a joint agreement to eliminate the geographical boundaries between each other in ASEAN. Malaysia is a neighboring country among ASEAN members and is an important importer of Thai products. Malaysia imports products from many major countries and Thailand accounting for 5.8 percent (Source: Office of Overseas Market Development 1, Department of International Trade Promotion). It is expected that in the future, the value of trade between Thailand and Malaysia will continue to expand, in line with the good expansion of the global economy. However, Thailand is a large exporter of goods and services to Malaysia and is popular as a business opportunity to drive product and service development and to expand the market continuously. Nakhon Pathom province has a 4-year provincial development strategy, 2015-2018, by focusing on the development of agriculture and processing industries to add value to products with safety, international standards, and environmental friendliness. the study realizes the importance of Nakhon Pathom community potential in the development of products for exporting to Malaysia.